The quest for gold - Fekete, Andrew, 1954-1986 (Liverpool University Press, 2016)
The Quest for Gold is an edited version of writings by visionary Andrew Fekete - a painter, architect, poet and writer - that occurs against the background of his sexuality and his membership of the gay community in London in the 1980s.